2013
DOI: 10.1016/j.ydbio.2012.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Gata3 directly regulates early inner ear expression of Fgf10

Abstract: The analysis of Fgf10 mouse mutants has demonstrated a critical role for this ligand in neurosensory development of the vertebrate inner ear, and we have been looking to define the direct upstream regulators of Fgf10 in this sensory organ, as part of constructing the programme of early inner ear development. Through the analysis of reporter constructs in transgenic mouse embryos and neonatal mice, in this report we define a minimal 1400 bp enhancer from the 5' flanking region of Fgf10. This enhancer drives rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…Exposure of embryos to RA at a stage where hindbrain patterning is either unaffected by RA exposure [25] or subsequent to hindbrain patterning, revealed that Fgf3 reporter activity is down regulated in the anteroventral otic vesicle but unaltered in the developing posterior hindbrain [26]. These findings support direct regulation of otic Fgf3 expression by RA, and underscore the importance of determining whether the response to RA may be mediated via binding to RA responsive elements located at the Fgf3 locus [16].In common with Fgf3, Fgf10 reporter expression is down regulated in the antero-ventral otic vesicle by exogenous RA during hindbrain patterning, but to a lesser extent after hindbrain patterning [24]. It will thus be interesting to further investigate whether the response to RA post-hindbrain patterning is direct on the otic Fgf10 enhancer or a secondary consequence of alterations in hindbrain pattern that lead to different signals influencing the development of the inner ear.…”
supporting
confidence: 51%
See 2 more Smart Citations
“…Exposure of embryos to RA at a stage where hindbrain patterning is either unaffected by RA exposure [25] or subsequent to hindbrain patterning, revealed that Fgf3 reporter activity is down regulated in the anteroventral otic vesicle but unaltered in the developing posterior hindbrain [26]. These findings support direct regulation of otic Fgf3 expression by RA, and underscore the importance of determining whether the response to RA may be mediated via binding to RA responsive elements located at the Fgf3 locus [16].In common with Fgf3, Fgf10 reporter expression is down regulated in the antero-ventral otic vesicle by exogenous RA during hindbrain patterning, but to a lesser extent after hindbrain patterning [24]. It will thus be interesting to further investigate whether the response to RA post-hindbrain patterning is direct on the otic Fgf10 enhancer or a secondary consequence of alterations in hindbrain pattern that lead to different signals influencing the development of the inner ear.…”
supporting
confidence: 51%
“…An issue is thus raised as to whether regulation of otic Fgf by RA may be direct or secondary to RA-induced changes in hindbrain pattern/specification. A more detailed understanding of the role of RA in regulating Fgf expression has been attained through analyses of reporter expression in mice containing lacZ either under the control of a minimal Fgf3 or Fgf10 enhancer [23,24]. Exposure of embryos to RA at a stage where hindbrain patterning is either unaffected by RA exposure [25] or subsequent to hindbrain patterning, revealed that Fgf3 reporter activity is down regulated in the anteroventral otic vesicle but unaltered in the developing posterior hindbrain [26].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore not surprising that the vestibuloacoustic ganglion is reduced in size in Fgf3 mouse mutants [5,21] and defects in vestibular sensory neurons and hair cells are produced following Fgf10 mutation [22]. Thus within the mouse, Fgf3 and Fgf10 are also required in a non-redundant manner for proper development within the otic epithelium as well as the earlier hindbrain-signalling events outlined above [23]. In addition, epithelial-derived FGF8 and FGF20, expressed in the presumptive epithelial domain of the organ of Corti, function in the specification of distinct cell types, in particular pillar cells, one of the supporting cells found in the developing auditory organ [24,25,26].…”
Section: Editorialmentioning
confidence: 99%
“…Otic capsule chondrogenesis can, however, be rescued by supplementation of cultures with a combination of FGF3 and FGF10 ligands, suggesting that these FGFs are indeed subject to control through RA signaling. Furthermore, recent studies show that the transcription factor GATA3 is a direct upstream regulator of Fgf10 that activates inner ear transcription [23].…”
Section: Editorialmentioning
confidence: 99%